Approach to Strengthen Community Participation of Teaching-Learning Process in Primary School - Suprapto Suprapto; Mohammad Viktor Farid Hakim (AL-ISHLAH: Jurnal Pendidikan, 2021)
The purpose of the study was to get the approach of community participation in Islamic Primary School North Ampenan. The participation of all parties greatly influences the success of the implementation of teaching and learning as an educational process in schools. The research method was used qualitatively. The data were collected through observation, interviews, and questionnaires. The participants involved were principals, teachers, parents, and school committees. Data analysis techniques consist of data reduction, data presentation, and concluding. While checking the validity of the data consists of credibility, dependability, confirmability, and transferability. The study results indicate that the approach required is centralized participation which refers to lifelong learning and integrated services. Various activities or community participation actions greatly influence implementing the education process at SDI Ampenan Utara, Mataram. The research implications are seen in the development of various community participation actions in building school quality.